Exchange‐Biasing in a Dinuclear Dysprosium(III) Single‐Molecule Magnet with a Large Energy Barrier for Magnetisation Reversal. Issue 30 (12th May 2020) - Han, Tian; Giansiracusa, Marcus J.; Li, Zi‐Han; Ding, You‐Song; Chilton, Nicholas F.; Winpenny, Richard E. P.; Zheng, Yan‐Zhen
Abstract: A dichlorido‐bridged dinuclear dysprosium(III) single‐molecule magnet [Dy2 L2 (μ‐Cl)2 (thf)2 ] has been made by using a diamine‐bis(phenolate) ligand, H2 L. Magnetic studies show an energy barrier for magnetisation reversal ( U eff ) around 1000 K. An exchange‐biasing effect is clearly seen in magnetic hysteresis with steps up to 3 K. Ab initio calculations exclude the possibility of a pure dipolar origin of this effect leading to the conclusion that super‐exchange through the chloride bridging ligands is important. Abstract : Single‐molecule magnet : A dichlorido‐bridged dinuclear dysprosium(III) single‐molecule magnet shows a new record of energy barrier for magnetisation reversal for polynuclear single‐molecule magnets. Moreover, the zero‐field tunnelling effect is suppressed by exchange‐biasing effect arising from magnetic coupling interactions between the Dy III centres.